A study on relationship between leadership styles towards employee performance at unifield education resources / Nur Aqila Shuib - Shuib, Nur Aqila (Faculty of Business and Management, 2020)
This research aim to discover the relationship between leadership types towards employee performance among employees at the Unifield Education Resources. The leadership styles divided into two independent variables which were autocratic and democratic and the dependent variable was employee performance. Leadership styles and employee performance were essential tools for the success of any organization in the long terms period. The study adopted correlation research design and simple random sampling were used. The target population was the employees in the organization. The researcher instrument used was questionnaires. Besides that, finding analysis includes reliability analysis, normality analysis, survey return rate, demographic analysis, correlational coefficient, multiple regression and hypothesis analysis. The researcher also used Statistical Package in the Social Science Software (SPSS) version 23.0 to analyse the data collected. The results derived from the data analyse revealed that there was a relationship between independent and dependent variable. Then, the researcher also made the recommendation for organization in order to improve and employee performance in the organization. The researcher also made recommendations for future research to improve the research study in the future.